THE EFFECT OF DISCUSSION TECHNIQUE AND ENGLISH LEARNING MOTIVATION TOWARD STUDENTS’ SPEAKING ABILITY - Menggo, S.; Ketut, Seken,; Made, Ratminingsih, (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
ABSTRACT The aim of this study is to investigate whether there is (1) a difference in the speaking ability between students who are taught by using discussion technique and those taught by using the conventional technique; (2) an effect of interaction between the speaking techniques applied and English learning motivation toward students? speaking ability; (3) a difference in speaking ability between students with high English learning motivation who are taught by using discussion technique  and those taught by using the conventional technique; and (4) a difference in speaking ability between students with low English learning motivation who are taught by using discussion technique and those taught by using the conventional technique. The study used a 2X2 factorial design, which involved a sample of 96 students. The data were collected by using questionnaire and a speaking test then analyzed by Two-way ANOVA. The result indicates that (1) there was a significant difference in speaking ability between the students who were taught by using discussion technique and those taught by using the conventional technique; (2) there was a significant interactional effect between the teaching techniques applied and students? motivation toward their speaking ability; (3) there was a significant difference in speaking ability between students with high English learning motivation who were taught by using discussion technique and those taught with the conventional technique; and (4) there was significant difference in speaking ability between the students with low English learning motivation who were taught by using discussion technique and those taught with the conventional technique.   Key words:  discussion technique, motivation, speaking ability